2022
DOI: 10.1177/20420986221107804
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ views on Self-administration of Medication during hospitalisation: a mixed-methods study

Abstract: Background: Inpatient Self-administration of Medication (SAM) increases patient involvement in medication management and may increase medication safety. Its implementation is impeded. Successful and sustainable implementation of SAM strongly depends on patients’ willingness to participate. This study aimed to identify and quantify patients’ views on SAM, related (dis)advantages and prerequisites, patient’s willingness to engage in SAM schemes, and their preferences in medication management during hospitalisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…We read the insightful study by Van Herpen-Meeuwissen et al , 1 in which a mixed-methods study regarded patient viewpoints on the self-administration of medication in a state of hospitalization. The results indicated that most of the patients in this study were optimistic about self-administering medication; however, some patients expressed concern about the safety of self-medication taking and questioned the need for change in the current approach to care in a hospital setting.…”
mentioning
confidence: 99%
“…We read the insightful study by Van Herpen-Meeuwissen et al , 1 in which a mixed-methods study regarded patient viewpoints on the self-administration of medication in a state of hospitalization. The results indicated that most of the patients in this study were optimistic about self-administering medication; however, some patients expressed concern about the safety of self-medication taking and questioned the need for change in the current approach to care in a hospital setting.…”
mentioning
confidence: 99%